Analisis Efektivitas Digitalisasi Faktur Pajak PPN dalam Meningkatkan Kepatuhan Pengusaha Kena Pajak (PKP) pada PT. ABC - Erica Diana Prayitno; Ulfa Puspa Wanti Widodo (Jurnal Mutiara Ilmu Akuntansi, 2024)
The purpose of this study is to evaluate the effectiveness of digitizing VAT fact sheets through the e-Faktur system in order to increase VAT sales revenue at PT. ABC. It is hoped that the digitization of tax invoices will have a positive impact on the effectiveness of tax administration and PKP thresholds. One of the data collection methods used is the qualitative descriptive method, which involves collecting data through observation and documentation. The findings of the study show that the implementation of e-Factur has successfully reduced the time needed to complete tax invoices from an average of seven days to two working days. In addition, the factorial error threshold decreased from 12% to 3%, indicating an increase in accuracy and efficiency. Increasing tax productivity at PT. ABC is also associated with ease of access and convenience in meeting tax requirements. Based on these results, this study shows that the digitization of tax facts through the effective use of e-Factur